Evaluating the Antimicrobial and Antibiofilm Efficacy of Lavender Essential Oil and Linalool on Dual Candida albicans Biofilms With Staphylococcus aureus and Staphylococcus epidermidis From Canine External Otitis - Navid Neisari; Aghil Sharifzadeh; Bahar Nayeri Fasaei; Sepideh Asadi; Alireza khosravi; Abolfazl Rafati Zomorodi; Javad Malakootikhah (Veterinary Medicine and Science)
ABSTRACT Background Biofilm formation significantly contributes to the rise of antimicrobial resistance, treatment failures and recurrent infections. Essential oils (EOs), particularly lavender EO (LEO), have gained attention for their antimicrobial and antibiofilm activities. This study investigates the effects of LEO and linalool on Staphylococcus aureus (S. aureus), Staphylococcus epidermidis (S. epidermidis), and Candida albicans (C. albicans) isolates. Materials and Methods The chemical composition of LEO was analysed using gas chromatography‐mass spectrometry (GC‐MS). Eight clinical and reference microorganisms were tested, including four C. albicans, three S. aureus, and three S. epidermidis isolates, to assess their biofilm‐producing potential with the tissue microtiter plate method. Antimicrobial and antibiofilm activities of LEO and linalool were evaluated in planktonic, single‐biofilm, and dual‐biofilm phases through microbroth dilution and scanning electron microscopy (SEM). Results The minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC) of LEO in the planktonic phase were 1250 µg/mL and 2500 µg/mL against Staphylococcus isolates, respectively, while the corresponding value for C. albicans isolates was 5000 µg/mL. 90% biofilm inhibition was achieved at concentrations of 5000 µg/mL and 40,000 µg/mL for Staphylococcus and C. albicans, respectively. LEO completely inhibited dual biofilms formed by C. albicans/S. aureus and C. albicans/S. epidermidis at 20,000 µg/mL, whereas linalool attained 100% inhibition at 40,000 µg/mL. Conclusion LEO demonstrates significant antimicrobial and antibiofilm activity against Staphylococcus and C. albicans isolates, effective in both planktonic and biofilm phases.